Lab observations on prolonged chrysalis diapause of Brahmaea (Acanthobrahmaea) europaea Hartig (Lepidoptera: Brahmaeidae) - Renato Spicciarelli (Fragmenta entomologica, 2018)
Brahmaea (Acanthobrahmaea) europaea Hartig, 1963, is an Italian endemic species exhibiting a very restricted geographic distribution (Basilicata and Campania regions, Grotticelle di Monticchio Nature Reserve and neighbouring areas), and developing as larvae on a few Oleaceae (Fraxinus angustifolia subsp. oxycarpa, Ligustrum vulgare and Phyllirea latifolia). From spring 2015 to spring 2017 a series of bioethological observations on the moth were conducted, as well as surveys aimed to study the distribution of its host plants in the habitats of SAC “Grotticelle di Monticchio”. In this short communication a prolonged diapause of B. europaea chrysalis kept in the laboratory is documented. In spring 2018, four successfully adult eclosions occurred from two years old pupae, a case never previously reported in literature records for this rare and threatened taxon.